Sport Training Individualization: State, Problems and Advanced Solutions - Erlikh, Vadim V.; Isaev, Alexander P.; Rybakov, Vladimir V. (Nomos Verlagsgesellschaft mbH & Co. KG, 2017)
This book covers the essence of sports training, new concepts and technologies, the prerequisites and scope of an individualised approach to training as well as how to integrate the main methodological paradigms of sports training systems using the theory of adaptation. Modernisation and analysis of a body’s potential plus features of efficient adaptation make it possible to adjust training loads and to ensure excellent sporting performances, particularly with the help of artificially controlled training environments. This book suggests the use of modern training methods in endurance sports. For example, it shows the benefits of focused application of exercises in developing local and regional muscular endurance, and provides recommendations on training for important competitions. It also describes the peculiarities of short-term reactions and the long-term adaptation of athletes to the techniques mentioned and to a higher level of performance.